ANALYSIS OF THE POTENTIAL AND MANAGEMENT STRATEGIES OF MANGROVE ECOTOURISM IN PANGKAL BABU AS A NATURE-BASED TOURISM VILLAGE FROM THE PERSPECTIVE OF ISLAMIC ECONOMICS IN KUALA TUNGKAL, TANJUNG JABUNG BARAT - Ghina Ulfa Saefurrohman; Mesi Agustina; Rizkio Kurniawan; Nabila Syafa Iranda (Journal on Islamic Economics, Finance & Banking [Z-CONOMICS], 2025)
This study aims to analyze the potential and management strategies of Mangrove Pangkal Babu Ecotourism as a nature-based tourism village in Kuala Tungkal, Tanjung Jabung Barat Regency, from an Islamic economic perspective. The research method used is descriptive qualitative, with data collected through literature studies and official government sources. The study shows that the Mangrove Forest of Pangkal Babu has significant potential as a sustainable ecotourism destination, supported by biodiversity, community involvement, and local government attention. Effective management strategies include raising public and visitor awareness to protect the mangrove forest, developing environmentally friendly tourism facilities, and creating job and business opportunities for local residents. From the perspective of Islamic economics, the management of this ecotourism site reflects the principles of justice ('adl), sustainability (istidamah), and balance (mizan), while avoiding excessive exploitation of natural resources. This study concludes that the development of Mangrove Pangkal Babu Ecotourism can serve as a model of sharia-based tourism that combines environmental conservation with equitable and sustainable community economic empowerment.